PERBEDAAN PERKEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN YANG MENGIKUTI PROGRAM KEWIRAUSAHAAN DENGAN YANG TIDAK MENGIKUTI PROGRAM KEWIRAUSAHAAN DI TK MAKARTI DAN DI TK PERTIWI KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - Fitriyani, Anggun; Kurnia, Rita; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a difference in the development of the creativity of children who follow the entrepreneurship program with those who do not participate in the entrepreneurship program in TK Makarti and in TK Pertiwi sub-district Kepenuhan of Rokan Hulu district. This research is quantitative research comparative research type. The sample of this study was 66 children and this study used a saturate sampling technique. The data collection techniquues used is observation sheets. Based on hypothesis test result abtained t count for 14,840, while t table (5%) (dk = n1 + n2 ? 2 = 30 + 36 -2 = 64) that is 2,000. Based on these calculations, there is a difference in the test calculate with t tabel (14,840>2,000). Then it can be see that there are difference between the development of creativity of children who follow the program with those who do not follow entrepreneurial program. Then Ha is rejected and is accepted, where Ha reads that there is a difference of development creativity children that join entrepreneurship program.Key Words: Creativity, Entrepreneurship